Health impact of US military service in a large population-based military cohort: findings of the Millennium Cohort Study, 2001-2008 - Amoroso Paul J; Wells Timothy S; Gackstetter Gary D; Smith Besa; Boyko Edward J; LeardMann Cynthia A; Hooper Tomoko I; Jacobson Isabel G; Smith Tyler C; Gray Gregory C; Riddle James R; Ryan Margaret AK (BMC, 2011)
Abstract Background Combat-intense, lengthy, and multiple deployments in Iraq and Afghanistan have characterized the new millennium. The US military's all-volunteer force has never been better trained and technologically equipped to engage enemy combatants in multiple theaters of operations. Nonetheless, concerns over potential lasting effects of deployment on long-term health continue to mount and are yet to be elucidated. This report outlines how findings from the first 7 years of the Millennium Cohort Study have helped to address health concerns related to military service including deployments. Methods The Millennium Cohort Study was designed in the late 1990s to address veteran and public concerns for the first time using prospectively collected health and behavioral data. Results Over 150 000 active-duty, reserve, and National Guard personnel from all service branches have enrolled, and more than 70% of the first 2 enrollment panels submitted at least 1 follow-up survey. Approximately half of the Cohort has deployed in support of operations in Iraq and Afghanistan. Conclusion The Millennium Cohort Study is providing prospective data that will guide public health policymakers for years to come by exploring associations between military exposures and important health outcomes. Strategic studies aim to identify, reduce, and prevent adverse health outcomes that may be associated with military service, including those related to deployment.